miR-23a-5p Alleviates Gouty Inflammation by Targeting Interleukin-17A and Inhibiting NLR Family Pyrin Domain Containing 3 Inflammasome Activation - Yuan, Xinzhu; Lin, Changwei; Zhang, Yanni; He, Hongni; Li, Lingqin (Archives of Rheumatology, 2025)
Background/Aims: Monosodium urate (MSU) is a key contributor to gout development, primarily by triggering innate inflammatory responses. Given the known role of miR-23a-5p in regulating inflammation, this study aimed to investigate the molecular mechanisms through which miR23a-5p influences MSU-induced gout inflammation. Materials and Methods: Monosodium urate was used to model gouty inflammation in THP-1 cells and Sprague–Dawley (SD) rats. In vivo, 15 SD rats were randomly divided into the control, model, model + miR-23a mimic, model + interleukin (IL)-17A, and model + miR-23a mimic + IL-17A groups. In vitro, the model cells were treated with miR-23a mimics, IL-17A, or both. TargetScan predicted that miR-23a-5p might target IL-17A, which was verified using a dual-luciferase reporter system. Subsequently, IL-17A and miR-23a-5p mRNA levels, as well as NLR family pyrin domain containing 3 (NLRP3) inflammasome–related factors (IL-1β, IL-6, NLRP3, IL-18, ASC, and caspase-1), were quantified using quantitative polymerase chain reaction, immunohistochemistry, enzyme-linked immunosorbent assay, and western blotting. Hematoxylin and eosin (H&E) staining was performed to observe pathological changes in rat ankles. Additionally, flow cytometry was conducted to quantify Th17 cells in rat blood. Results: Both in vivo and in vitro, miR-23a-5p expression was downregulated, whereas IL-17A expression was upregulated in the gout models. The H&E staining revealed that miR-23a-5p mimic treatment alleviated gout symptoms, whereas IL-17A treatment exacerbated these symptoms. Direct interaction between miR-23a-5p and IL-17A was validated using a dual-luciferase reporter assay. Moreover, flow cytometry analysis showed that miR-23a-5p overexpression inhibited Th17 cell differentiation. Additionally, miR-23a-5p suppressed NLRP3 inflammasome activation by targeting IL-17A. Correspondingly, the expression of proinflammatory proteins such as IL-1β, IL-6, NLRP3, IL-18, and caspase-1 was downregulated by miR-23a-5p and upregulated by IL-17A treatment. Conclusion: This study demonstrated that miR-23a-5p alleviates MSUinduced gouty inflammation by directly targeting IL-17A. Through this regulation, miR-23a-5p suppresses NLRP3 inflammasome activation, highlighting its potential as a therapeutic target for gout. Cite this article as: Yuan X, Lin C, Zhang Y, He H, Li L. MiR-23a-5p alleviates gouty inflammation by targeting interleukin-17A and inhibiting NLR family pyrin domain containing 3 inflammasome activation. Arch Rheumatol. 2025;40(4):443-451.